2022
DOI: 10.14444/8302
|View full text |Cite
|
Sign up to set email alerts
|

Is Sarcopenia a Risk Factor for Postoperative Surgical Site Infection After Posterior Lumbar Spinal Fusion?

Abstract: Background: This retrospective observational study aimed to evaluate the impact of sarcopenia on surgical site infection (SSI) risk in patients who undergo posterior lumbar fusion. While many studies have investigated the impact of sarcopenia on postoperative morbidity both in general and orthopedic surgery, none of them examined the risk of postoperative infection after lumbar spine surgery in sarcopenic vs nonsarcopenic patients.Methods: Consecutive 55-to 75-year-old patients who underwent short posterior lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…[8][9][10][11] Despite the large heterogeneity of current studies, initial literature in spine surgery has demonstrated that sarcopenia may serve as an independent prognostic factor for increased rates of osteoporotic fractures, increased health care costs, and nonhome discharge. [12][13][14] For example, a study of patients who suffered from osteovertebral fracture after dorsal spine instrumentation determined sarcopenia, as defined by EWGSOP criteria of SMA (skeletal muscle area) and SMD (skeletal muscle density), a prognostic marker of instrument failure. 12 Two further retrospective studies analyzed the rates of complications in patients undergoing short-segment posterior arthrodesis for lumbar degenerative disease when stratifying for sarcopenia as measured through the psoas lumbar vertebral index (PLVI).…”
Section: Complications and Health Care Usementioning
confidence: 99%
See 3 more Smart Citations
“…[8][9][10][11] Despite the large heterogeneity of current studies, initial literature in spine surgery has demonstrated that sarcopenia may serve as an independent prognostic factor for increased rates of osteoporotic fractures, increased health care costs, and nonhome discharge. [12][13][14] For example, a study of patients who suffered from osteovertebral fracture after dorsal spine instrumentation determined sarcopenia, as defined by EWGSOP criteria of SMA (skeletal muscle area) and SMD (skeletal muscle density), a prognostic marker of instrument failure. 12 Two further retrospective studies analyzed the rates of complications in patients undergoing short-segment posterior arthrodesis for lumbar degenerative disease when stratifying for sarcopenia as measured through the psoas lumbar vertebral index (PLVI).…”
Section: Complications and Health Care Usementioning
confidence: 99%
“…13,14 Both studies only consisted of ~300 patients, and determined surgical site infections were not found to be linked to sarcopenia; however, one study demonstrated sarcopenic patients were more likely to have increased operative times and inpatient length of stay (LOS). 13,14 Furthermore, 2 further retrospective studies demonstrated that sarcopenia, as assessed through the PLVI, increased total inpatient hospital cost, LOS, and rates of nonhome discharge. 15,16 Given the relatively recent introduction of a designated ICD code for sarcopenia in 2016, there is a current lack of large database analysis analyzing the independent risk of sarcopenia for complications and health care use.…”
Section: Complications and Health Care Usementioning
confidence: 99%
See 2 more Smart Citations
“…12 Two further retrospective studies analyzed the rates of complications in patients undergoing short-segment posterior arthrodesis for lumbar degenerative disease when stratifying for sarcopenia as measured through the psoas lumbar vertebral index (PLVI). 13,14 Both studies only consisted of ~300 patients, and determined surgical site infections were not found to be linked to sarcopenia; however, one study demonstrated sarcopenic patients were more likely to have increased operative times and inpatient length of stay (LOS). 13,14 Furthermore, 2 further retrospective studies demonstrated that sarcopenia, as assessed through the PLVI, increased total inpatient hospital cost, LOS, and rates of nonhome discharge.…”
Section: Complications and Health Care Usementioning
confidence: 99%